Co-teaching: Perspectives from Speech-Language Pathologists on the Conditions Influencing Its Development - González-Fernández, Daniela; Gambetta-Tessini, Karla; Iturra, Carolina (Revista de Investigación en Logopedia, 2025)
Co-teaching is a collaborative pedagogical strategy that involves educators and speech-language pathologists working jointly to support the inclusion of students with disabilities in mainstream classrooms. Its implementation provides opportunities for ongoing professional development of educators and enhances classroom dynamics. However, its advancement has been in its early stages, and various factors have impacted its progress. This study explored the sociodemographic variables and intervention conditions that might influence the participation of speech-language pathologists in the classroom setting. Data from 505 speech-language pathologists working in educational environments were collected through an online questionnaire. Binary regression was used to identify the sociodemographic conditions and characteristics of the intervention that affect the entry of speech-language pathologists into the classroom. The findings indicate that 58% (n=295) of the speech-language pathologists surveyed enter the classroom to engage in activities alongside the teachers. Moreover, it was discovered that the availability of time and the frequency of meetings with classroom teachers were statistically significant conditions for the development of co-teaching. The study emphasizes the importance of collaboration and joint planning between teachers and speech-language pathologists to facilitate co-teaching. It highlights that effective management of time and resources is crucial for successful classroom integration, suggesting the necessity for policies and practices that support these conditions to enhance inclusive education. These results provide a clear and concise framework for promoting the entry of speech-language pathologists into the classroom.
Keywords: Co-teaching; Speech-language pathologist; Teacher